Islamic Religious Education Teacher’s View and Learning Action on Puritan Fiqh in Madrasa - Rozi, Syaikhu; Yaqin, Ainul (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2022)
This research aims to analyze the views, attitudes and approaches of PAI teachers in teaching the materials of fiqh which are puris in madrasa. The research was carried out qualitatively based on phenomenological research design. Researchers withdrew the data by conducting in-depth interviews with Fiqh teachers at Madrasah Aliyah. Furthermore, researchers also utilized documentation of textbooks used by teachers. They also distribute questionnaires via google form. Consequently, it concluded that, Fiqh teachers generally in Mojokerto have moderate religious views and attitudes. There were three types of approaches used by teachers in teaching the materials of puritan fiqh. First, the contextual approach which was assumed to be able to form a moderate character and tends to be liberal for students. Second, the textual approach, the implications of it can lead students to have fundamentalist perspective. Third, the integration of textual and contextual can influence students' perspectives to be moderate based on wasathiyah principles. By having moderate views and attitudes and supported by the integration of contextual and textual approach, it can form a moderate perspective of students. Then, this research rejected the anxiety that Islamic Religious Education can create puritanical Islamic teaching. It also rejected the claim that the radicalization process was carried out through madrasa.